Gender and racial differences in peer effects of limited English students: A story of language or ethnicity? - Timothy M. Diette; Ruth Uwaifo Oyelere (IZA Journal of Migration, 2017)
There is a perception among native born parents in the USA that the increasing number of immigrant students in schools creates negative peer effects on their children. In North Carolina, there has been a significant increase in immigrants, especially those with limited English language skills. Recent data suggests that North Carolina has the eighth largest English-language learner (ELL) student population and over 60 % of immigrants are from Latin America and the Caribbean. While past research suggests negative though negligible peer effects of Limited English (LE) students and black students on the achievement of other students, potential peer effects of students from Latin America in general have not been considered. In this paper, we attempt to identify both LE student and Latin American (LA) student peer effects by separately utilizing fixed effects methods that allow us to deal with the potential selectivity across time and schools. On average, we find no evidence of negative peer effects of LE students on females and white students but note small negative effects on average on males and black students. We also find that, holding constant other factors, an increase in the share of LA students does not create negative peer effects on native students' achievement. Rather, it is the limited English language skills of some of these students that lead to small, negative peer effects on natives.
Keywords: I20; I21; J15; J24; 330; Immigrants; Student achievement; Peer effects; Education; Race; Gender; Limited English students; Latino peer effects; Hispanic peer effects